Disclosure practices in Bangladesh: A critical review on Islamic insurance companies (IIUC Business Review, 2022)
The aim of the study is to analyze the reporting and disclosure practices in Islamic insurance (takaful) companies in Bangladesh. The accounting system is not the same for the both conventional and Islamic insurance companies as the principles and functions of takaful are different from the traditional one. The study included five Islamic insurance companies out of six as the sample organizations by using purposive sampling method. The un-weighted disclosure index (UDI) method has been used to grade the sample organizations on their disclosures in the annual reports for the period from 2015 to 2019. MS excel has been used to analyze the data. Despite their common regulatory rules, some differences have been found in presenting their reports of the sample Islamic insurance companies. According to UDI value, on the whole disclosure status of the selected insurance companies are good. This study found that the deviations in reporting in the selected takaful companies are not insignificant. The increasing trend of disclosure of the takaful companies bears the good indication.IIUC Business Review, Vol.-11, Issue-1, Dec. 2022, pp. 113-126